1993
DOI: 10.1177/00220345930720110401
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Central Nervous System in the Salivary Secretion Induced by Pilocarpine in Rats

Abstract: The effect of rats of an anteroventral third ventricle (AV3V) electrolytic lesion on salivary secretion induced by intraperitoneal (i.p.) or intracerebroventricular (i.c.v.) injection of a cholinergic agonist (pilocarpine) was investigated. Sham- or AV3V-lesioned rats anesthetized with urethane and with a stainless steel cannula implanted into the lateral ventricle (LV) were used. The amount of salivary secretion was studied over a seven-minute period after i.c.v. or i.p. injection of pilocarpine. In sham-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 11 publications
1
35
0
1
Order By: Relevance
“…It has been demonstrated that pilocarpine, when injected intracerebroventricularly (icv), produced salivary secretion at a significantly higher level than control (11,16). It has also been reported that electrolytic lesion of the AV3V produced a decrease in salivary flow induced by pilocarpine injected icv (11). These results indicate that other areas of the CNS, such as the areas surrounding the third ventricle, are important for pilocarpine-induced salivary secretion.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been demonstrated that pilocarpine, when injected intracerebroventricularly (icv), produced salivary secretion at a significantly higher level than control (11,16). It has also been reported that electrolytic lesion of the AV3V produced a decrease in salivary flow induced by pilocarpine injected icv (11). These results indicate that other areas of the CNS, such as the areas surrounding the third ventricle, are important for pilocarpine-induced salivary secretion.…”
Section: Discussionmentioning
confidence: 97%
“…Pilocarpine at a concentration of 40 µg produced a medium salivary flow, whereas the flow rate increased in a linear fashion up to 160 µg. It has been demonstrated that pilocarpine, when injected intracerebroventricularly (icv), produced salivary secretion at a significantly higher level than control (11,16). It has also been reported that electrolytic lesion of the AV3V produced a decrease in salivary flow induced by pilocarpine injected icv (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta mesma lesão também atenua o aumento da pressão arterial, ingestão de água, natriurese e caliurese induzida pela injeção intracerebroventricular (icv) de carbacol (agonista colinérgico) 4 e mesmo ativação colinérgica de diversas áreas prosencefálicas, como área septal medial (ASM), órgão subfornical (OSF), hipotálamo ventro-medial (HVM) e área preóptica lateral (APL) 22/25 , ou caudais como locus coeruleus 26 . A lesão aguda da região AV3V também reduz a salivação induzida pela pilocarpina (intraperitoneal ou icv), o que tem contribuído para suportar a sugestão de que parte do efeito sialogogo deste agonista colinérgico depende também de uma ação central do mesmo 27,28 . Embora a lesão da região AV3V prejudique respostas pressoras de diversas origens, os animais com lesão aguda da região AV3V podem apresentar um pequeno aumento da pressão arterial acompanhada de taquicardia nos primeiros dias após a lesão 21 .…”
Section: -Importância Da Região Av3v Efei-tos Da Lesão Eletrolíticaunclassified
“…11,12 It was reported that pilocarpine, a muscarinic agonist, injected intracerebroventricularly (icv) induced salivary secretion by activating central autonomic efferent fibres. 13 Cannabis consumption has been associated with a reduction in salivary flow and may lead to oral problems like progressive dental caries, fungal infection, oral pain, and dysphagia. 14,15 The main psychoactive ingredient of Cannabis sativa, D9-tetrahydrocannabinol (THC), affects different physiological functions.…”
Section: Introductionmentioning
confidence: 99%